Letter : Basque Children's Funds - Newman, A. E.
029-0091-001 Registered Office: 1 Balloon St, Manchester, 4. Telegraphic Address: "WHOLESALE" E.D.O. London. Telephone Royal 7221 EXTENSION NO 254 Please address Your Reply Co-operative Wholesale Society Limited. BRANCH ADMINISTRATIVE OFFICE, 99 Leman Street, London, E.1. Our Reference: A/AEN/VAB Your Reference 23rd November, 1937. Dear Mr. Tewson, BASQUE CHILDREN'S FUNDS. For your information we beg to give you below particulars of the items ordered by you recently, from which you will see that the amount has exceeded £5. 0. 0, by a few shillings.- 1½ doz. Shorts Navy. @ 29/11 = £2. 4. 11. 3 only Skirts. @ 4/11 = £ 14. 9. 1 only Skirt @ 4/11 = 4. 11. 2½ doz. 3x7 Wool Gloves @ 8/11 = £1.2. 3. 1¼ doz. Pyjamas 5x9 @ 17/11 = £1.2. 5. TOTAL = £5. 9. 3. Yours faithfully, pro Society. A.E. Newman Mr. H. V. Tewson, Trades Union Congress, Transport House, Smith Square, S.W.1. 292/946/29/91